Resolving discharge parameters from atomic oxygen emission. (25th June 2021) - Viegas, P; Vialetto, L; van de Steeg, A W; Wolf, A J; Bongers, W A; van Rooij, G J; van de Sanden, M C M; Diomede, P; Peeters, F J J
Abstract: A method is proposed to spatially resolve discharge parameters from experimental measurements of emission intensity and 1D numerical simulations including an O atom collisional-radiative model. The method can be used for different plasmas and conditions. Here, contracted microwave discharges for CO2 conversion are studied at intermediate to high pressures (100–300 mbar). Radial profiles of electron density ( n e ) are used as input in the model and corrected to successfully simulate the measured Gaussian profiles of emission intensity of the 777 nm transition ( I 777 ). As a result, radially-resolved parameters inaccessible in experiments, such as n e, power density ( P abs ), electron temperature ( T e ), electric field and reaction rates, are numerically-obtained for several conditions. n e and P abs approximately follow Gaussian profiles that are broader than that of I 777 . For pressures below 150 mbar, the difference in full width at half maximum is typically a factor 1.6. This consists in a phenomenon of optical contraction, which is due to concave profiles of O molar fraction and T e . The implications of the simulated profiles on the study of plasmas for CO2 conversion are discussed and it is shown that these profiles allow to explain high reactor performances at low pressures.